Correction: Supportive care during pediatric hematopoietic stem cell transplantation: beyond infectious diseases. A report from workshops on supportive care of the Pediatric Diseases Working Party (PDWP) of the European Society for Blood and Marrow Transplantation (EBMT) - Nava, Tiago; Ansari, Marc; Dalle, Jean-Hugues; de Heredia, Christina Diaz; Güngör, Tayfun; Trigoso, Eugenia; Falkenberg, Ulrike; Bertaina, Alice; Gibson, Brenda; Jarisch, Andrea; Balduzzi, Adriana; Boenig, Halvard; et al. (Bone marrow transplantation, 2020)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.